Biopsy-proven IgG4-related lung disease. Issue 1 (December 2016) - Sun, Xuefeng; Liu, Hongrui; Feng, Ruie; Peng, Min; Hou, Xiaomeng; Wang, Ping; Wang, Hanping; Xu, Wenbing; Shi, Juhong
Abstract Background Immunoglobulin G4-related disease (IgG4-RD) is a fibroinflammatory disorder that may involve single or multiple organs. Biopsy-proven lung involvement of this disease is occasionally reported, but not well understood. Methods Patients with the diagnosis of biopsy-proven IgG4-related lung disease (IgG4-RLD) from Peking Union Medical College Hospital between January 2011 and July 2015 were retrospectively analyzed. Age, sex, clinical symptoms, laboratory findings, pulmonary function test results, chest CT tests, positron emission tomography (PET) examinations, treatments and prognoses were retrieved from medical records and analyzed. Results Seventeen patients were included in this study (mean age: 44.8 ± 15.0 years). Ten patients were diagnosed via surgery, and 7 patients were diagnosed via percutaneous transthoracic core-needle lung biopsy. Extrapulmonary involvement was observed in only one patient. The clinical symptoms included cough, fever, dyspnea, chest pain and hemoptysis. The serum IgG4 concentration was elevated in 7/13 patients (mean: 1955 ± 1968 mg/L). The chest CT findings included mainly nodules and masses with spiculated borders, alveolar consolidations with air bronchograms, and ground glass opacities with or without reticular opacities. PET scans indicated increased standardized uptake values, and 7/8 patients were correctly diagnosed with benign inflammation. Corticosteroids and immunosuppressants were administered to 14/17 patients and effectively alleviated the disease. Conclusions In biopsy-proven IgG4-RLD, a normal serum IgG4 concentration is commonly seen, while extrapulmonary involvement is infrequent. Alveolar consolidation with air bronchograms is an important imaging finding of IgG4-RLD, which has not been emphasized before.